ANALISIS PEMBELAJARAN BERBASIS ARTIFICIAL INTELLIGENCE DI SEKOLAH MENENGAH ATAS GRACIA - Thomas, Thomas (JURNAL KOULUTUS, 2025)
The purpose of this study is to determine the extent to which students are familiar with and utilize AI in the learning process both inside and outside of school. This research done at SMA Gracia Tangerang conducted using a quantitative research approach. The results of this study indicate that Artificial Intelligence has a significant impact on the student learning process, where based on simple linear regression analysis, it was found that the significance value of 0.01 is smaller than 0.05 and the calculated t-value of 8.985 is greater than the t-table value of 2.021, thus H1 (the hypothesis) is accepted. From this study, it can be concluded that students at Gracia Senior High School have become well-acquainted with learning using AI, resulting in a significant improvement in the quality of education at Gracia Senior High School.